Relationship between change management initiatives and job satisfaction among employees in banking sector at Malacca / Mazurah Mohammad - Mohammad, Mazurah (Faculty of Office Management and Technology, 2017)
The purpose of this study is to identify the relationship between change management initiatives and job satisfaction among employees and also to find out the level of job satisfaction. The change management initiatives include the communication, up-line support and shared vision. This study required 150 employees from banking sector at Malacca to be the representatives. The workers in banking sector is the most suitable sampling frame because they provide a service and faces with technology that require change to satisfy the customers. Thus, to require change a steps should be make in order to prevent job turnover and increase the employee’s satisfaction. A questionnaire was used as an instrument in this study to collect the information. Plus, the sampling technique for this study is convenience. Then, the data was analyzed by using SPSS 21. The results of this analysis shows that job satisfaction is correlate with communication, up-line support and shared vision. This research will provide valuable information regarding the relationship between change management initiatives and address the level of employees’ job satisfaction. In addition, a recommendation for the current study was provided as reference for the organization and the researcher. There are two suggestions for the current study, in which the study should include a mediate factor between the elements in change initiatives. Meanwhile, it was suggested that the organization, should improve communication in the workplace. Other than that, the researcher also offering a recommendation for the future study, which is to be use simple random sampling technique in the study. Moreover, it was suggested that for the next researcher to apply open-ended question in order the respondent could express their feeling.